Liquid‐Phase Beam Pen Lithography. Issue 8 (7th January 2016) - He, Shu; Xie, Zhuang; Park, Daniel J.; Liao, Xing; Brown, Keith A.; Chen, Peng‐Cheng; Zhou, Yu; Schatz, George C.; Mirkin, Chad A.
Abstract : Beam pen lithography (BPL) in the liquid phase is evaluated. The effect of tip‐substrate gap and aperture size on patterning performance is systematically investigated. As a proof‐of‐concept experiment, nanoarrays of nucleotides are synthesized using BPL in an organic medium, pointing toward the potential of using liquid phase BPL to perform localized photochemical reactions that require a liquid medium.